2020
DOI: 10.21203/rs.3.rs-45636/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of Controlled Hypertension on Hemostasis Before Closure of the Operative Incision in Patients Undergoing Vertical Partial Laryngectomy: A Randomized Controlled Study

Abstract: Background: To evaluate the efficacy of controlled hypertension on hemostasis before closure of the operative incision in vertical partial laryngectomy (VPL).Methods: Seventy males scheduled for VPL were randomly assigned to Group H who received either ephedrine or phenylephrine to maintain a mean arterial pressure (MAP) of 90–110 mmHg 10 min before the operative incision closure or to Group N who received normal saline. The primary endpoint was the volume of drainage after surgery. Heart rate, MAP, surgical f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Some studies have suggested that the Trendelenburg position is sensitive to the identification of bleeding vessels and is involved in bleeding control (8,14,15). However, a longer duration of this position may limit the procedure due to the risk of high intracranial pressure (11,15). Therefore, in the present study, the Trendelenburg position of 30 degrees was used for 4 min.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Some studies have suggested that the Trendelenburg position is sensitive to the identification of bleeding vessels and is involved in bleeding control (8,14,15). However, a longer duration of this position may limit the procedure due to the risk of high intracranial pressure (11,15). Therefore, in the present study, the Trendelenburg position of 30 degrees was used for 4 min.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, Ozdemir et al (2017) stated that the Valsalva maneuver helps detect more bleeding points after the Trendelenburg position (11), and therefore, reduces bleeding. Some studies have suggested that the Trendelenburg position is sensitive to the identification of bleeding vessels and is involved in bleeding control (8,14,15). However, a longer duration of this position may limit the procedure due to the risk of high intracranial pressure (11,15).…”
Section: Discussionmentioning
confidence: 99%